Pengaruh Harga dan Kualitas Pelayanan Terhadap Keputusan Penggunaan Jasa Mahardhika Creative Event Organizer di Bandar Lampung - Kesuma, Renaldy Rafif; Lestari, Tri (Jurnal EMT KITA, 2025)
This research aims to find out how price and quality influence the decision to use services at Mahardika Creative Event Organizer. In this research, there are 2 independent variables tested, namely the influence of price and service quality. This research uses a quantitative approach with descriptive methods. This research was also conducted at PT. Mahardika Creative Event. Data collection techniques in this research used questionnaires, literature studies, and interviews. The results of this research show that the influence of price and service quality has a significant effect on the decision to use services at Mahardika Creative Event Organizer.